Heart rate variability in essential hypertensive patients with ischaemic hemisphere stroke - V. V. Syvolap; S. P. Zhemanyuk; M. S. Potapenko (Zaporozhye State Medical University, 2016)
Objective. The aim of the study is to determine heart rate variability (HRV) parameters in essential hypertensive patients with ischaemic hemisphere stroke; and to observe the role of suprasegmental and segmental dysregulation depending on cerebral and cardiac disorders. Materials and methods. This study recruited 103 inadequately controlled essential hypertensives (mean age 60.39±10.74 years) and 41 essential hypertensive (EH) patients with acute ischaemic hemisphere stroke (mean age 62.41±10.36 years), and also 15 individuals of comparable age without EH (mean age 59.66±6.51) - healthy volunteers. ABPM was recorded using a bifunctional device (Incart, S.-P., R. F.). Time-domain, frequency-domain indices of HRV were calculated. Results. There was statistical difference in diurnal SDNN (P=0.012), for daytime period (P=0.034); in diurnal SDANN (P=0.001), for daytime period (P=0.006); the circadian index (P<0.001), in diurnal rMSSD (P=0.05) and for daytime period (P=0.01) in EHs with stroke in comparison to healthy volunteers. Furthermore, there was an association between right hemisphere damage and increasing diurnal and daytime LF/HF index (113.8 and 86.7 %, respectively), and also decreasing parasympathetic parameters in comparison with the parameters of left hemisphere damage stroke patients. Conclusion. There is a reduction in HRV parameters in essential hypertensive patients with acute ischaemic hemisphere stroke, meanwhile there is an increasing of the parasympathetic part of nervous system. Also, there is no significant difference in SDNN, SDANN, rMSSD and the heart rate for the nighttime period in stroke individuals as compared with healthy volunteers. Moreover, right hemisphere ischaemic stroke parameters of HRV associate with the activation of the sympathetic part of nervous system over 24 hours. At the same time, there is a decreasing of HRV parameters of the parasympathetic part of nervous system in this category of patients.